Relação entre agronegócios sustentáveis e os direitos de propriedade intelectual: um estudo de plantas transgênicas - Carvalho Neto, Gil Ramos de (2011)
A sustainable agribusiness must be concerned with all its branches, including the production and negotiation of agricultural biotechnologies. The study of transgenic plants theme brings up several issues that affect society today in regard to environmental, economic and social sustainability. The field of CTS studies seeks public awareness of the relationship between science, technology and society, taking into account the risk society we live in, and the process of reflexive modernization which we pass through. The law must comply with its regulatory function in the area, taking into account social expectations. The promulgation, on March 24, 2005, of the Biosafety Law (Law nº 11.105/2005) that proposes to establish safety standards and enforcement mechanisms of activities involving genetically modified organisms, is an initiative towards that path. This work, which is based on the technological monitoring of transgenic plants on the basis of patents from the National Institute for Intellectual Property, from the enactment of this Act, in addiction to analyzing the regulatory mark for those technologies in order to verify the possibility of dual protection of them, through the LPI and by the system of LPC. It was identified a concentration of patent filings on behalf of foreign companies, pointing to the need of an analysis of the risks from not only the technology itself, but also the know-how of technological products arising from genetic engineering. Concerning to the legal intellectual protection, this dissertation, according to the methodology used study of laws didn´t find any gaps that would enable the double protection of transgenic plants.